The isotope record (δ13C, δ18O) of vertical mobility in incremental tissues (tooth enamel, hair) of modern livestock: A reference set from the Mongolian Altai. (10th September 2021) - Lazzerini, N.; Coulon, A.; Simon, L.; Marchina, C.; Fiorillo, D.; Turbat, Ts; Bayarkhuu, N.; Noûs, C.; Lepetz, S.; Zazzo, A.
Abstract: Identifying the isotopic signatures of vertical mobility and alpine meadows exploitation in the teeth of domesticated animals can be a key to understanding the subsistence strategies used by pastoral communities through history. Indeed, the oxygen (δ 18 O) and carbon (δ 13 C) isotopic composition of sequentially sampled tooth enamel, used alone or in combination have been commonly employed to investigate altitudinal mobility and alpine exploitation. However, conflicting interpretations of the outcomes of these analyses exist, due in part to the paucity of modern reference datasets. In this study, we propose a new reference set, composed of GPS monitored sheep, goats and horses from the Mongolian Altai, to investigate the influence of vertical mobility and mean grazing altitude, on the C and O isotopic compositions of sequentially sampled tooth enamel and on the C isotopic composition of horse tail hair. We found that δ 13 C values were negatively correlated with the mean grazing altitude and time of residency of alpine meadows. Although no correlation was found between the average δ 18 O values of tooth enamel and mean grazing altitude, vertically mobile livestock had a higher intra-tooth range in δ 18 O values than vertically immobile livestock, possibly reflecting the ingestion of isotopically more diverse sources of water. Moreover, the coefficient of the correlation between δ 13 C and δ 18 O values of tooth enamel was - although weakly - negatively correlated with the standard deviation of the animal mean grazing altitude (i.e. reflecting the frequency of altitudinal mobility). These results confirm that δ 13 C and δ 18 O analyses of tooth enamel and tail hair can be used to infer animal mobility and land use in modern and ancient times.